2001
DOI: 10.1023/a:1005529016641
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Liquid diet (LD) is known to be protective against indomethacin-induced enteropathy, which is thought to be associated with ischemic change. We tested the hypothesis that the solid component of diet modulates small intestinal blood flow (SIBF) following indomethacin administration. In the first experiment, male Wistar rats were divided into 18-hr-fasted and normal diet groups. Indomethacin (20 mg/kg) or vehicle was administered intracolonically. SIBF was measured on both the mesenteric and antimesenteric sides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The mechanisms of the toxicity and resistance to aluminum have been widely studied (for reviews, see [2][3][4][5][6][7][8]). Although the toxic effects of aluminum have been recognized for 70 years, the reasons for this toxicity are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of the toxicity and resistance to aluminum have been widely studied (for reviews, see [2][3][4][5][6][7][8]). Although the toxic effects of aluminum have been recognized for 70 years, the reasons for this toxicity are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This toxic effect is not yet completely understood, in spite of the knowledge that Al-toxicity is involved with cell processes like inhibition of root elongation and cell division [55,56], nutrient-induced deficiency poor nutrient uptake [57], interaction with cytoskeleton [58] and inhibition on signal transduction events [12] among others. In the same sense it has been reported that Si can ameliorate Al-toxicity under certain conditions in species like barley (Hordeum vulgare; [59]), soybean (Glycine max; [60]), maize (Zea mays; [61]) and sorghum (Sorghum bicolor; [62]).…”
Section: Al Affects the Phospholipid Signaling Pathwaymentioning
confidence: 99%
“…It is never found naturally as a free metal but rather is always present as aluminium silicate or as a silicate of Al mixed with other metals such as sodium, potassium, iron, calcium or magnesium [4]. Aluminium toxicity is the most important growth-limiting factor for plants in highly acidic soils [5][6][7]. The cumulative data on Al-interactions indicates that Al has a significant effect on different signal transduction pathways such as phosphoinositide [8,9], protein phosphorylation [10] and polyamines [11,12], and that anion channels may participate in these interactions by excreting organic acids as an Al-tolerance mechanism in plants [13][14][15].…”
Section: Introductionmentioning
confidence: 99%